Case Report: Identification of a Novel ODAD3 Variant in a Patient With Primary Ciliary Dyskinesia - Wang, Rongchun; Yang, Danhui; Guo, Ting; Lei, Cheng; Chen, Xu; Kang, Xi; Qing, Jie; Luo, Hong (Frontiers in Genetics, 2021)
Background:ODAD3 encodes a protein of 595 amino acids and contain three highly conserved coiled-coil domains, which is essential for cilia axoneme dynein arm assembly and docking. Primary ciliary dyskinesia (PCD) of ODAD3 deficiency are rarely reported. Female infertility in PCD related to ODAD3 variants has not been reported. Methods: Whole-exome and Sanger sequencing were used to identify the disease-related gene of the patient with PCD in a consanguineous Chinese family. Domain analysis was applied to predict the impact of the variant on ODAD3 protein. Results: The 35 year-old female patient exhibited chronic sinusitis, diffuse bronchiectasis, dextrocardia and infertility. We identified a novel homozygous variant in ODAD3, c.1166_1169dupAGAC, p.(Leu391Aspfs*105) in the PCD patient by exome sequencing and Sanger sequencing. This frameshift variant was predicted to be disease causing by bioinformatics analysis and was also not presented in the current authorized large genetic databases. Conclusions: Our study enriches the genetic spectrum and clinical phenotypes of ODAD3 variants in PCD and provide more evidence for future genetic counseling and gene-targeted therapy for this disease.